(untitled) (Research, Society and Development, 2020)
Therapy awakens archetypes and psychic functions unknown to human consciousness. In this way, this article aims thinking about the relationship between religiosity and the healing process in the therapeutic period, using the archetype of the wounded healer. The therapist, by activating his own wounds, initiates a healing process with the patient, in a set of projections and transferences. Reading productions of Carl Gustav Jung and Analytical Psychology authors, it was possible to delineate the theoretical study. The therapist, playing the patient’s transcendent function role, leads him to activate his archetype of the wounded healer, the image of a religious transcendence.